2015
DOI: 10.1017/s0022215115003394
|View full text |Cite
|
Sign up to set email alerts
|

Facial nerve management in jugular paraganglioma surgery: a literature review

Abstract: No strict guidelines for facial nerve management in jugular paraganglioma resection are available. Although long anterior rerouting provides the best tumour exposure along with a low morbidity rate, case-by-case selection of the surgical approach is recommended.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(16 citation statements)
references
References 33 publications
1
14
0
1
Order By: Relevance
“…Our patient got partial FN function improvement from H-B grade V to II at the last follow-up visit. The partial recovery might be due to partial compensation of viable intrinsic arterial plexus of the FN for extrinsic blood supply interruption, as proposed by Odat et al [ 2 ]. However, residual paresis might be explained by prolonged ischemia caused by Onyx or anterior rerouting of the FN itself which deprives the nerve from its extrinsic blood supply.…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…Our patient got partial FN function improvement from H-B grade V to II at the last follow-up visit. The partial recovery might be due to partial compensation of viable intrinsic arterial plexus of the FN for extrinsic blood supply interruption, as proposed by Odat et al [ 2 ]. However, residual paresis might be explained by prolonged ischemia caused by Onyx or anterior rerouting of the FN itself which deprives the nerve from its extrinsic blood supply.…”
Section: Discussionmentioning
confidence: 94%
“…Jugular paragangliomas (JPs) are slow-growing highly vascular tumors that can cause extensive invasion of the surrounding vital structures [ 1 ]. The gold standard of treatment is complete surgical resection with pre-operative embolization [ 2 ]. When the tumor is inoperable, or the patient is unfit for surgery, radiotherapy or superselective embolization can be alternative primary treatment options [ 3 ].…”
Section: Introductionmentioning
confidence: 99%
“…6 Llorente et al 7 found no difference in the surgical exposure attained or the tumor removal possible by mobilizing (rerouting) the temporal part of the facial nerve. Contradicting this are studies of cadaveric dissection by Von Doersten and Jackler, 8 which quote a wider corridor for surgery and lesion removal as well as fewer recurrences 9 on rerouting the facial nerve. It has also been suggested that removal of the bone around the jugular bulb and carotid canal cannot be done satisfactorily without facial nerve rerouting.…”
Section: Discussionmentioning
confidence: 99%
“…Non-rerouting approaches permitted the preservation of the facial nerve function in all patients of the present series. A recent review of the literature reported HB grade I-II in 95% of the non-rerouting approaches at the cost of a significant increase of persistence 7 . Consequently, even if conservative approaches could be performed in selected C1 TJPs, the rerouting of the nerve allows an acceptable functional and cosmetic result in 69% of the cases and should be therefore always performed (Table 4.2.2.III).…”
Section: Advancements and Open Issuesmentioning
confidence: 99%